The Effects of Javanese turmeric (Curcuma xanthorriza Roxb) on fibroblasts, granulation, blood vessel density, and contraction in wound healing of STZ-induced diabetic rats: DOI: 10.48129/kjs.15261 - Kristianto, Heri; Husnul Khotimah; Ryharti A. Sholeha; Eky W. Mardianto; Hasnah C. Sani; Hardika A. Paratiwi (Kuwait Journal of Science, 2022)
Diabetic ulcers usually occur in the lower extremities of diabetic patients. One in 20 diabetic patients will develop an ulcer, and 10% of those cases lead to amputation. This study aimed to investigate the effects of Javanese turmeric (Curcuma xanthorriza) extract on the number of fibroblasts, granulation, blood vessel and the rate of wound contraction in a Wistar rat model of the diabetic ulcer. This was an experimental study with post-test observations only and randomized control group design. Rats were divided into five groups: (1) negative control; (2) positive control; (3) P1; (4) P2; and (5) P3. Every rat was assessed for fibroblast number, granulation, blood vessel density, and wound contraction percentage. Javanese turmeric extract had a significant effect on histological parameters (fibroblast, blood vessels and tissue granulation) (p < 0.05) and wound contraction (p < 0.05). The double linear test revealed a significant relationship between fibroblasts, granulation, blood vessel quantity, and wound contraction (p < 0.05). Correlation and regression tests showed that Javanese turmeric extract explained 91% of the effects on fibroblasts, blood vessels, and granulation. Treatment with Javanese turmeric extract increased the number of fibroblasts, tissue granulation, blood vessel density and wound contraction in male diabetic wistar rats.